International graduates host country employment intentions and outcomes: Evidence from two Australian universities. Issue 5 (3rd September 2019) - Cameron, Roslyn; Farivar, Farveh; Coffey, Jane
ABSTRACT: A key attractor for many international students when choosing to study abroad is the prospect of gaining employment in the host country after graduating. From a university's perspective this becomes an important attraction issue for both maintaining and increasing the number of international students as well as improving graduate employability. A survey was utilised to explore employment intentions and outcomes of international graduate alumni from two Australian universities (n = 511 and n = 648). A comparative analysis between the universities has been undertaken in relation to this and rates of unemployment amongst graduates. The study has coined the term Two-step migration intender for international students/graduates and contributes to a gap in the research in relation to international graduate mobility, career intentions and employment outcomes. The findings have strategic implications for the promotion of Australian higher education to overseas markets and can also inform higher education policy and practice in terms of strategies for promoting international graduate employability.